2017
DOI: 10.1186/s12935-016-0372-8
|View full text |Cite
|
Sign up to set email alerts
|

miR-324-3p suppresses migration and invasion by targeting WNT2B in nasopharyngeal carcinoma

Abstract: BackgroundNasopharyngeal carcinoma (NPC) is a malignant epithelial carcinoma of the head and neck with strong ability of invasion and metastasis. Our previous study indicated that miR-324-3p, as a tumor-suppressive factor, could regulate radioresistance of NPC cells by targeting WNT2B. The purpose of this study is to investigate the role of miR-324-3p on migration and invasion in NPC cells.MethodsQuantitative real time PCR was applied to measure the expression level of miR-324-3p and WNT2B mRNA in both cells a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 30 publications
0
45
0
Order By: Relevance
“…Therefore, we confirmed the migration capacity of T98G-R and U87-R cells, and similarly found significant reduction of the scratch marks compared to that of T98G and U87 cells ( Figures 1F,G ). Meanwhile, the protein expression of E-cadherin, a migration inhibitor, and Vimentin, a pro-migration factor ( Liu et al, 2017 ), was also examined by western blot to estimate the degree of epithelial-to-mesenchymal transition (EMT). As expected, we found that T98G-R and U87-R displayed a lower level of E-cadherin and much higher level of Vimentin compared to their parental T98G and U87 cells ( Figure 1H ).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we confirmed the migration capacity of T98G-R and U87-R cells, and similarly found significant reduction of the scratch marks compared to that of T98G and U87 cells ( Figures 1F,G ). Meanwhile, the protein expression of E-cadherin, a migration inhibitor, and Vimentin, a pro-migration factor ( Liu et al, 2017 ), was also examined by western blot to estimate the degree of epithelial-to-mesenchymal transition (EMT). As expected, we found that T98G-R and U87-R displayed a lower level of E-cadherin and much higher level of Vimentin compared to their parental T98G and U87 cells ( Figure 1H ).…”
Section: Resultsmentioning
confidence: 99%
“…Wnt/β-catenin signaling pathway is a key driver for cancer behaviors in numerous malignancies 30 , which is also intensively studied in our previous researches about radioresistance and metastasis of SCCHN 26 , 31 , 32 . Recent publication indicates that PVT1 promotes chemoresistance in bladder urothelial carcinoma via Wnt/β-catenin signaling pathway 33 .…”
Section: Resultsmentioning
confidence: 99%
“…For example, miR-212 could suppress HCC growth via targeting FOXA1 [ 7 ]. And a research revealed that miR-129-2 might serve as a prognostic indicator for HCC patients and exerted a tumor suppressive role by inhibiting high mobility group box 1 (HMGB1) [ 24 ].What’s more, miR-324-3p has been suggested to be involved in tumorigenesis and tumor development by acting as an oncogene or tumor suppressor in several cancers, such as nasopharyngeal carcinoma [ 9 , 25 ], colorectal cancer [ 26 ] and lung squamous cell carcinoma [ 10 ]. Especially, Wen Y et al highlight that miR-324-3p is significantly overexpressed in the HBV-positive HCC patients compared with the HBV-positive cancer-free controls in both the training and validation sets [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…And miR-15b-5p regulates HCC growth and metastasis through the AKT/mTORC1 and β-catenin signaling pathways [ 8 ]. Recently, Liu C et al reported that miR-324-3p could modulate cancer cell growth and apoptosis by targeting SMAD family member 7 (SMAD7) in nasopharyngeal carcinoma [ 9 ]. Gao X et al demonstrated that up-regulated miR-324-3p expression was an independent prognostic predictor for early stage lung squamous cell carcinoma [ 10 ].…”
Section: Introductionmentioning
confidence: 99%